Making Morocco : colonial intervention and the politics of identity - Wyrtzen, Jonathan, 1973- (Cornell University Press, 2015)
How did four and a half decades of European colonial intervention transform Moroccan identity? As elsewhere in North Africa and in the wider developing world, the colonial period in Morocco (1912-1956) established a new type of political field in which notions about and relationships among politics and identity formation were fundamentally transformed. Instead of privileging top-down processes of colonial state formation or bottom-up processes of local resistance, the analysis in Making Morocco focuses on interactions between state and society. Jonathan Wyrtzen demonstrates how, during the Protectorate period, interactions among a wide range of European and local actors indelibly politicized four key dimensions of Moroccan identity: religion, ethnicity, territory, and the role of the Alawid monarchy. This colonial inheritance is reflected today in ongoing debates over th the public role of Islam, religious tolerance, and the memory of Morocco's Jews; recent reforms regarding women's legal status; the monarchy's multi-culturalist recognition of Tamazight (Berber) as a national language alongside Arabic; the still-unresolved territorial dispute over the Western Sahara; and the monarchy's continued symbolic and practical dominance of the Moroccan political field. -- Inside jacket flaps.